2015
DOI: 10.1007/s00247-015-3352-6
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of acoustic radiation force impulse (ARFI) elastography to the ultrasound diagnosis of biliary atresia

Abstract: The addition of ARFI to a standard abdominal US in the initial workup of the neonate with possible infantile cholestasis can provide reliable information on liver fibrosis and help in the diagnosis of biliary atresia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 23 publications
0
33
0
Order By: Relevance
“…In children, Noruegas et al reported that the mean SWV value of healthy liver was 1.11 m/s . Hanquinet et al measured the mean SWV value of liver as 1.12 m/s (range: 0.73–1.45 m/s) for children . Matos et al determined the mean SWV value of liver as 1.07 ± 0.10 m/s for a healthy pediatric population, with the possibility of reaching 1.12 m/s in the case of younger children .…”
Section: Discussionmentioning
confidence: 99%
“…In children, Noruegas et al reported that the mean SWV value of healthy liver was 1.11 m/s . Hanquinet et al measured the mean SWV value of liver as 1.12 m/s (range: 0.73–1.45 m/s) for children . Matos et al determined the mean SWV value of liver as 1.07 ± 0.10 m/s for a healthy pediatric population, with the possibility of reaching 1.12 m/s in the case of younger children .…”
Section: Discussionmentioning
confidence: 99%
“…Close follow up is required post-liver transplantation, for autoimmune liver diseases, alpha-1 antitrypsin deficiency and cystic fibrosis [30,31]. Patients with biliary atresia, which is the most common cause of neonatal obstructive jaundice, would also benefit from non-invasive follow-up assessment after the Kasai portoenterostomy to determine the best timing for liver transplantation [29,32]. Regarding the indications, contraindications and the technique used, we refer to the published literature [33][34][35][36][37][38][39][40][41].…”
Section: Possible Indications For Shear Wave Elastography (Swe) Measumentioning
confidence: 99%
“…Noninvasive quantitative methods such as point shear wave elastography are used to measure tissue stiffness . An alternative method of biopsy in children is becoming increasingly necessary.…”
mentioning
confidence: 99%